POSITION OF IN-THE-BAG POSTERIOR CHAMBER INTRAOCULAR LENSES RELATIVE TO THE LIMBUS: Applications to Scleral-Sutured Lenses. Issue 7 (July 2021) - Vingopoulos, Filippos; Nair, Archana; See, Craig W.; Iyengar, Nishanth; Haberman, Ilyse; Sperber, Laurence; Lazzaro, Douglas R.; Singh, Rishi; Ho, Allen; Gupta, Omesh; Sharma, Sumit; Modi, Yasha
Abstract : Purpose: To characterize the true position of in-the-bag intraocular lenses (IOLs) relative to the limbus using ultrasound biomicroscopy and estimate scleral-sutured IOL positioning. Methods: This prospective single-center study included 70 eyes of 41 patients with in-the-bag posterior chamber IOLs. Four vertical ultrasound biomicroscopy captures were performed in each eye in the superior, inferior, nasal, and temporal quadrants. Postoperative biometric data were collected. The primary outcome was the vertical distance of the in-the-bag IOL from the sclerocorneal limbus. Secondary outcomes included anterior shift and refractive change of a theoretical scleral-sutured IOL using sclerotomies at 2.5 mm and 3 mm posterior to the limbus. Results: A total of 265 ultrasound biomicroscopy images were analyzed, including 64 superior, 69 inferior, 66 nasal, and 66 temporal. The true in-the-bag IOL position measured as distance posterior to the sclerocorneal limbus was 4.23 ± 0.56 mm superiorly, 4.22 ± 0.46 mm inferiorly, 3.95 ± 0.48 mm nasally, and 3.86 ± 0.52 mm temporally. The anterior shift of a theoretical scleral-sutured IOL was 0.60 mm for a 3-mm sclerotomy and 0.93 mm for a 2.5-mm sclerotomy, resulting in a theoretical myopic shift of 0.45 diopter (D) and 0.79 D, respectively, assuming a 15-D IOL. Larger biometric measurements correlated with a more posterior in-the-bag position. Conclusion: True in-the-bag IOL position was found to be more posterior than estimates of scleral-sutured IOLs. Additional corrections in scleral-sutured IOL calculations may improve refractive outcomes. Abstract : True in-the-bag intraocular lens position, measured with ultrasound biomicroscopy, was consistently more posterior to the limbus (3.5–4 mm) than the position of sclerotomies currently used (3 mm). To offset the ensuing myopic surprises often reported in scleral-sutured intraocular lenses, we recommend adjustments in secondary intraocular lens formulas.